Responsibility and the hidden politics of directionality: opening up ‘innovation democracies’ for sustainability transformations - Andy Stirling (Journal of Responsible Innovation)
Developing earlier work, this paper explores analytic and political implications of ideas about direction in innovation. Unduly hidden in mainstream innovation and sustainability transformations literatures, crucial issues arise for responsible innovation. Although essential to both rigour and effectiveness, key realities tend to be concealed by general hegemonic forces in contemporary global colonial modernity, as well as by more specific expediencies to power and privilege in particular settings. To help resist these obscuring pressures, three contrasting (frequently conflated) meanings are distinguished. Directing innovation involves driving narrow motivating processes towards some given end. The direction of innovation concerns broader steering of pathways towards more openly chosen ends. Directionality of innovation entails grasping deeper political potentialities spanning pluralities of ends. Seriously eroding innovation policy and research alike, much current governance activity fails appropriately to focus or act on these distinctions. To assist greater policy robustness and legitimacy, this paper points to important (but often neglected) practises in each regard. To properly address social and ecological sustainability imperatives, greater attention is advocated to irreducibly political aspects of responsible innovation. This entails renewed emphasis not only on precaution, participation and accountability, but on actively supporting emancipatory struggle towards plural ‘directions for progress’ in innovation democracies.